Social Learning Through Stakeholder Engagement: New Pathways from Participation to Health Equity in U.S. West Coast HIA - Nicole Iroz-Elardo, PhD; Moriah McSharry McGrath, PhD, MPH, MSUP (Indiana University-Purdue University Indianapolis, 2016)
While some contend that extensive public engagement activities are necessary to meet Health Impact Assessment (HIA) practice standards, other work suggests that an HIA of any type hasthe potential to inform decision-making in ways that embody HIA's value of democracy (Cole & Fielding, 2007; Harris-Roxas et al., 2012; Negev, 2012). These divergent perspectives on how to realize democracy through public participation represents an area of evolving debate in the ongoing development of HIA practice in the US. Looking to the relatively diverse HIA practice on the west coast of the US, we explore the interplay between engagement strategies and HIA values in completed HIAs. We locate each HIA on Harris-Roxas's (2011) typology of HIAs - mandated, decision-support, advocacy, and community-led - and assess the type(s) and extent of participation activities conducted. This sample incorporates a variety of both HIA types, target policy/program decisions in different sectors, and HIAs conducted by seasoned and novice practitioners.